Solving Differential Equation via Orthogonal Branciari Metric Spaces - Senthil Kumar Prakasam; Arul Joseph Gnanaprakasam; Gunaseelan Mani; Santosh Kumar (Journal of Function Spaces)
In this paper, we investigate an orthogonal L⋆-contraction map concept and prove the fixed-point theorem in an orthogonal complete Branciari metric space (OCBMS). We also provide illustrative examples to support our theorems. We demonstrated the existence of a uniqueness solution to the fourth-order differential equation using a more orthogonal L⋆ contraction operator in OCBMS as an application of the main results.